ASSESSING THE ROLE OF MENTAL ACCOUNTING IN ENTREPRENEURIAL DEVELOPMENT IN THE NIGER DELTA (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
Mental accounting reflects a series of cognitive operations that help organize financial activities and facilitate money management. However, empirical evidence linking mental accounting and small business growth are scarce. The present study aimed to investigate mental accounting as an accounting strategy that could enhance the development of small-scale enterprises in the Niger Delta, Nigeria. The study employed a cross-sectional survey design. Eighty-seven (n=87) small and medium-scale operators randomly selected from the Niger Delta Regions participated in the survey. The respondents completed a self-report questionnaire. A simple linear regression model was used for data analysis. The result indicated that mental accounting significantly predicted the growth of small business enterprises at β = .912, p< .05, with R2 indicating that mental accounting contributed 13.1% of the variation in the growth of small business enterprises. Implications and recommendations are discussed